2020
DOI: 10.1038/s12276-020-0417-x
|View full text |Cite
|
Sign up to set email alerts
|

PRMT7 deficiency causes dysregulation of the HCN channels in the CA1 pyramidal cells and impairment of social behaviors

Abstract: HCN channels regulate excitability and rhythmicity in the hippocampal CA1 pyramidal cells. Perturbation in the HCN channel current (I h ) is associated with neuropsychiatric disorders, such as autism spectrum disorders. Recently, protein arginine methyltransferase 7 (PRMT7) was shown to be highly expressed in the hippocampus, including the CA1 region. However, the physiological function of PRMT7 in the CA1 neurons and the relationship to psychiatric disorders are unclear. Here we showed that PRMT7 knockout (KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Furthermore, PRMT7 is involved in stress response and its inhibition significantly reduced levels of Heat Shock Protein 70 (HSP70) stress-associated proteins [ 82 ]. Discoveries regarding PRMT7 and the nervous system have been reported recently, with PRMT7 shown to be highly expressed in the hippocampus [ 83 ]. Lee et al have shown that PRMT7 regulates HCN channels in CA1 hippocampal pyramidal cells, which could have implications for neuropsychiatric disorders [ 83 ].…”
Section: Functional Significance Of Arginine Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PRMT7 is involved in stress response and its inhibition significantly reduced levels of Heat Shock Protein 70 (HSP70) stress-associated proteins [ 82 ]. Discoveries regarding PRMT7 and the nervous system have been reported recently, with PRMT7 shown to be highly expressed in the hippocampus [ 83 ]. Lee et al have shown that PRMT7 regulates HCN channels in CA1 hippocampal pyramidal cells, which could have implications for neuropsychiatric disorders [ 83 ].…”
Section: Functional Significance Of Arginine Methylationmentioning
confidence: 99%
“…Discoveries regarding PRMT7 and the nervous system have been reported recently, with PRMT7 shown to be highly expressed in the hippocampus [ 83 ]. Lee et al have shown that PRMT7 regulates HCN channels in CA1 hippocampal pyramidal cells, which could have implications for neuropsychiatric disorders [ 83 ]. Additionally, PRMT7 has been shown to interact with the Beta-catenin-C-Myc axis and promote the growth of renal cell carcinoma (RCC) [ 84 ].…”
Section: Functional Significance Of Arginine Methylationmentioning
confidence: 99%
“…The PRMT7 inhibitor DS-437 (GLPBIO, GC45927, Montclair, CA) was dissolved at 100 mM in DMSO and stored. The concentration of drug administered was 10 mM and 100 mM, 19,39 as obtained by diluting the stock solution (DMSO # 0.1%). DS-437 was incubated with the neurons for 1 hour before current-clamp recordings.…”
Section: Drug Administrationmentioning
confidence: 99%
“…Muscles derived from PRMT7 −/− mice displayed decreased oxidative metabolism [ 67 ]. In addition, Lee and colleagues reported that PRMT7 −/− mice showed hyperactivity as well as social interaction defects [ 68 ]. These findings demonstrate that PRMT7 −/− mice have defects in bone and skeletal muscle mass, delayed or impaired neuronal development, increased adipogenesis, and possibly also reduced male fertility.…”
Section: The Roles Of Prmt7 In Developmentmentioning
confidence: 99%
“…Further analysis showed that PRMT7 was highly expressed in the CA1 field of the hippocampus, and PRMT7 −/− mice displayed defects in social behaviors [ 78 ]. Recent studies further revealed that PRMT7 −/− CA1 neurons exhibited HCN (hyperpolarization-activated, cyclic-nucleotide-gated) channel current dysfunction, which might be attributed to the decreased HCN protein levels mediated by SHANK3 downregulation [ 68 , 79 ]. These findings provide insights into the role and the underlying mechanisms of PRMT7 functioning in neuronal development.…”
Section: The Roles Of Prmt7 In Developmentmentioning
confidence: 99%